Potential Application of Essential Oils for Mitigation of Listeria monocytogenes in Meat and Poultry Products - Yousefi, Mojtaba; Khorshidian, Nasim; Hosseini, Hedayat (Frontiers in Nutrition, 2020)
One of the most important challenges in the food industry is to provide healthy and safe food. Therefore, it is not possible to achieve this without different processes and the use of various additives. In order to improve safety and extend shelf-life of food products, various synthetic preservatives have been widely utilized by the food industry to prevent growth of spoilage and pathogenic microorganisms. On the other hand consumers’ preference to consume food products with natural additives, induced food industries to use natural-based preservatives in their production. It has been observed that plant extracts and their essential oils could be potentially considered as a replacement of chemical antimicrobials. Antimicrobial properties of plant essential oils is derived from some main bioactive components such as phenolic acids, terpenes, aldehydes and flavonoids that presented in the essential oils. Therefore, in this studied the effect of various essential oils and their bioactive components against Listeria monocytogenes in meat and poultry products is reviewed.